Evaluasi Desain Antarmuka Pengguna pada Situs Web Kabupaten Malang menggunakan Metode Human Centered Design (HCD) - Ayuningtyas Ayuningtyas; Satrio Hadi Wijoyo; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
A district of Malang is a government located in province of East Java. Malang is the second largest district in East Java after Banyuwangi. As a government, Malang applies e-Government for improved information services for this government. There are 2 pages there often accessed by users, it is a home page and potential area page. A problem on district of Malang website is a placed of content that too dense, lacking an explanation of information, inconsistent use of language and font type, and improper color combination. A reference method which use for Malang district is Human Centered Design (HCD). HCD is a method used to design new interface that user needs. Thereafter do the usability testing on the first and last evaluation. There are 3 metrics usability used as parameter of success is effectivity, efficiency, and satisfaction. Result shown for first evaluation success is 58,4%, non critical error is 16,6%, and a critical error is 23,3%. And for last evaluation success is 100%, non critical error is 0%, and critical error is 0%. Efiiciency metric enchance 90% after website improvement. A satisfaction metric for first design reach non acceptable grade, and an improved interface design reach acceptable grade.